Preferensi Petani terhadap Karakteristik Varietas Padi Unggul di Lahan Rawa Pasang Surut - Rina, Yanti; Koesrini, Koesrini (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2018)
Indonesian Swampland Agricultural Research Institute is one of the UPT-Technical Implementation Unit conducting UPBS Management Unit of Extension Seed which provide swamp rice seed.The object of research was to study the preference of farmer on the characterization of 12 varieties in tidal swampland.The researchwas conducted on farmerâ€™s fields at Bunga Karang village, Mandastana district, Barito Kuala regency,and the survey was at Samuda village, Belawang district, Barito Kuala regency in 2016. Thirty-three farmers were be taken randomly as respondent. Characteristics of farmers, plant morphology, yield and texture of rice were collected as primary data source by observation and interview. The data were analyzed descriptively.The preference of farmers to plant morphology such as plant type, plant height, tillers and panicle length of all varieties were preferred by both Javanese and Banjarese farmers, except Inpara 1 and Inpara 5.Â For plant age preference, except Inpara 4, all varieties were preferred by respondents. Meanwhile Inpara 5, Inpara 7, Mekongga, and Ciherang were not preferred varieties by all farmers according to resistence to pests (stem borer and Leptocorisa oratorius) and diseases (blast). All farmers preferredthe physical of grain, rice quality, color, and taste of rice.